The Impact of Return on Asset, Debt to Equity Ratio, Book Value of Equity per Share, and Dividend Payout Ratio towards the Stock Price of LQ-45 Companies Listed in the IDX Period 2014 - 2016 - Yunita Vilanie (iBuss Management, 2018)
Yuk Nabung Saham, a campaign conducted by IDX invites the society to invest in stocks. Hence, the society needs an insight about company’s financial condition to help it in deciding which company’s stock to invest and monitoring the company’s stock price. A measurement that frequently used by the investors and analyst to measure its financial condition is financial ratio. This condition encourages the researcher to find categories of financial ratio that could affect the company’s stock price. Thus, the researcher aims to study the impact of return on asset, debt to equity ratio, dividend payout ratio, and book value of equity per share towards the stock price of LQ-45 companies listed in the IDX period 2014 - 2016.The research has collected the data of 19 companies consistently listed in the LQ-45 index during the period of 2014-2016 and analyzed using multiple linear regressions. The result shows that return on asset, debt to equity ratio, dividend payout ratio, and book value of equity per share simultaneously give a significant impact towards the stock price. While individually, return on asset, debt to equity ratio, and book value of equity per share give a significantly positive impact towards the stock price. Keywords: Return on Asset, Debt to Equity Ratio, Dividend Payout Ratio, Book Value of Equity per Share, Stock Price